Noise-immune cavity-enhanced optical heterodyne detection of HO2 in the near-infrared range. - Bell, C; van Helden, J; Blaikie, T; Hancock, G; van Leeuwen, N; Peverall, R; Ritchie, G (2012)
Accurate measurements of the absolute concentrations of radical species present in the atmosphere are invaluable for better understanding atmospheric processes and their impact on Earth systems. One of the most interesting species is HO(2), the hydroperoxyl radical, whose atmospheric daytime levels are on the order of 10 ppt and whose observation therefore requires very sensitive detection techniques. In this work, we demonstrate the first steps toward the application of external-cavity diode-laser-based noise-immune cavity-enhanced optical heterodyne molecular spectroscopy (NICE-OHMS) to the detection of the HO(2) radical in the near-infrared range. Measurements of stable species and of HO(2) were made in a laboratory setting, and the possibilities of extending the sensitivity of the technique to atmospheric conditions are discussed.